Unravelling (E-)Government Channel Selection: A Quantitative Analysis of Individual Customer Preferences in Germany and Australia - Plattfaut, Ralf; Kohlborn, Thomas; Hofmann, Sara; Beverungen, Daniel; Niehaves, Björn; Räckers, Michael; Becker, Jörg (46th Hawaii International Conference on System Sciences, 2013)
The purpose of this study is to identify the impact of individual differences on service channel selection for e-government services. In a comparative survey of citizens in Germany and Australia (n=1205), we investigate the impact of age, gender, and mobility issues on the selection of personal or mobile communication as channels for service consumption. The results suggest that Australians are more likely to want to use new technology-oriented channels as internet or mobile applications while Germans tend to use classical channels as telephone or in person. Moreover, differences with respect to age, gender, and mobility exist. Implications for practice and issues for future research are discussed.